Analisis Pelatihan, Motivasi, dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan - Rahmansyah, Andrean; Wahyono, Teguh; Rahayu, Sri (STAI Darul Kamal NW Kembang Kerang, 2024)
The aim of this research was to analyze the influence of training, motivation and work discipline on employee work productivity at PT. Perkebunan Nusantara IV Regional 1 Medan. The approach used is quantitative descriptive in the form of numbers and statistical analysis using SPSS Version 25. The population of this research is all 36 employees. Meanwhile, the sampling for this research is probability sampling using saturated sampling. The results of this study show that training has no effect and is not partially significant on employee work productivity with a value of tcount> ttable (1.792>2.036) and motivation has no effect and is not partially significant on employee work productivity with a value of tcount> ttable (0.770>2.036). and work discipline has a positive and partially significant effect on employee work productivity with a value of tcount> ttable (2.568>0.015). Simultaneously training, motivation and work discipline have a positive and significant effect on employee work productivity with a value of fcount>ftable (29.936 > 2.90). The magnitude of the influence exerted between variables with an R2 value of 71.3% and the remaining 28.7% is explained by other independent variables not examined in this study.